Challenges of Financing Public Education in Kwara State: Options and Implications for Development. - Atolagbe, Adedapo Adetiba; Oparinde, Olayiwola; Oyeniran, Saheed; Omosidi, Abdulraman (NIU Journal of Social Sciences, 2017)
The adoption of socialist approach to the supply of education in Kwara State since the beginning of the new civilian administration in 1999 has led to the increase in school environment at all levels of education. The government desire to meet her social responsibility in this direction has necessitated an increased in her financial commitment to the sector. This was carefully x-rayed by this paper with particular attention to the secondary school sub sector. The study found a need for alternative financing options and sustainable strategies to keep current funding patters alive. The paper recommended cost sharing model as an alternative financing strategy as well as efficiency based funding options. It concluded that if alternative strategies are adopted, more financial resources will be generated and available to fund schools at the current level. Also funds previously locked up in secondary education sector will be free for use in other sectors of education currently being under-funded. Key words: Budget, Capital Expenditure, Recurrent Expenditure, Actual Budget Released, Budget Estimate.